Implementasi Teknologi Dalam Evaluasi Program Pendidikan Di Man Insan Cendekia Jambi - Aris Munandar; Aldi Agustino; Asrijal Asrijal; Etri Dwi Sestia; Eyzi Havizah; Indah Uswatun Khasanah; Lusdawati Lusdawati; Misda Yanti; M. Yusuf; Novita Sari (Journal on Education, 2024)
This research examines the application of technology in the context of evaluating educational programs at Madrasah Aliyah Negeri Insan Intellectuals (MAN ICJ). Through this study, we explore the role and impact of technology in improving the educational program evaluation process at MAN ICJ. This research uses a qualitative approach by collecting data through observation, interviews and document analysis. The research results reveal that the use of technology, such as online education applications and data management systems, has helped increase efficiency in the collection, analysis and reporting of evaluation data. In addition, technology also provides opportunities to involve various stakeholders, such as students, teachers and parents, in the evaluation process. These findings provide valuable insight into how technology can be an effective tool for optimizing educational program evaluation at MAN ICJ while increasing transparency and accountability in education. Research shows that the use of technology, such as educational management systems and online evaluation tools, has made a positive contribution to improving the measurement of educational outcomes, monitoring student progress, and providing more timely feedback to stakeholders. These findings underline the importance of technology integration in the educational context and evaluation of educational programs at MAN ICJ. This study can be a guide for similar institutions that want to maximize the potential of technology in an effort to improve the quality of education.